If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 6)(5x + 4) = 0 Reorder the terms: (6 + 2x)(5x + 4) = 0 Reorder the terms: (6 + 2x)(4 + 5x) = 0 Multiply (6 + 2x) * (4 + 5x) (6(4 + 5x) + 2x * (4 + 5x)) = 0 ((4 * 6 + 5x * 6) + 2x * (4 + 5x)) = 0 ((24 + 30x) + 2x * (4 + 5x)) = 0 (24 + 30x + (4 * 2x + 5x * 2x)) = 0 (24 + 30x + (8x + 10x2)) = 0 Combine like terms: 30x + 8x = 38x (24 + 38x + 10x2) = 0 Solving 24 + 38x + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(12 + 19x + 5x2) = 0 Factor a trinomial. 2((3 + x)(4 + 5x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(4 + 5x)' equal to zero and attempt to solve: Simplifying 4 + 5x = 0 Solving 4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 0 + -4 5x = 0 + -4 Combine like terms: 0 + -4 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8Solution
x = {-3, -0.8}
| -45+(-5)= | | (5n+3)(2n-1)= | | (2x+5)=0 | | 12+6(z-2)=-3z+5 | | 24x=-56 | | 2c-16*4=7 | | (-1-3i)+2(4+6i)= | | 7x+3.5= | | 100x=34 | | 2(2x+1)+x=x+2x+18 | | 100m-49n= | | -16x=18 | | 2.03+6r*7=2.09 | | 4(5c+2)-12=18c+4 | | 22x=15 | | 11=80x | | -5(t+1)=5 | | 13=-3x | | x^4-x^2=12 | | 1=24x | | 11x+2-10x=-14 | | 4a^2-12a+9=4 | | 12x^3y-75xy^3= | | 5x-5y=-9 | | 2*(2x)+10=3x+13 | | -5x+2y=11 | | -10x=-10 | | x+8=2x-10 | | 27x=-1 | | 14=2x-9 | | 32=2x-10 | | 20u+18v= |